Sociology Teachers’ Comprehension of Ecological Literacy in Sociology Learning in Senior High Schools in Indonesia: A Critical Pedagogic Study - Ghufronudin Ghufronudin; Siany Indria Liestyasari; Atik Catur Budiati; Dwi Astutik; Bagas Narendra Parahita (FKIP Universitas Lampung, 2026)
Climate change and the rapid acceleration of environmental degradation have underscored the necessity of educational strategies that foster ecological awareness and critical engagement among students. Sociology, a social science discipline that investigates the relationship between society and environmental concerns, offers a strategic framework for integrating ecological literacy. The objective of this investigation is to investigate the perceived comprehension of ecological literacy among Sociology teachers and to investigate the integration of ecological literacy into the teaching of Sociology in senior high schools from the perspective of critical pedagogy. The design of this investigation was mixed-methods. A survey was administered to Sociology instructors to collect quantitative data regarding their perceived comprehension of ecological literacy and its integration into classroom practices. Qualitative data were collected through participative observations, in-depth interviews, focus group discussions, and document analysis of instructional materials and lesson plans. The data were analyzed using descriptive statistics and an interactive qualitative analysis model that included data reduction, data visualization, and conclusion drawing. The veracity of the findings was improved through the triangulation of data sources. The results suggest that the majority of teachers reported a high level of perceived comprehension of ecological literacy and acknowledged its significance in addressing environmental and climate-related challenges. Teachers frequently urged students to critically examine environmental issues, social inequalities, and human-environment interactions. Nevertheless, the analysis of documents and classroom observations demonstrated a discrepancy between the pedagogical implementation and curriculum planning. Despite the inclusion of ecological issues in lesson plans, classroom practices frequently prioritized conceptual comprehension over transformative action. The main challenges that emerged were the insufficient institutional support, limited instructional resources, and restrictions on critical classroom dialogue. The research demonstrates that critical pedagogy offers a valuable framework for integrating ecological literacy into Sociology education by promoting environmental responsibility and critical consciousness. The results are a valuable addition to the ongoing discourse regarding ecological education, curriculum development, and teacher professional development. Future research should investigate instructional strategies that enhance the implementation of ecological literacy and assess their long-term influence on students' ecological awareness and transformative action. Keywords: ecological literacy, critical pedagogy, sociology learning.